The Implementation of Critical Literacy Approach towards EFL College Students - Desak Made Yeni Wardani (English Education Department STKIP Agama Hindu Singaraja, 2021)
Literacy is a crucial aspect in English education that concerns the ability to read, write, then integrate and link what they have learned to daily life. However, several researchers found that there was a lack of literacy activity in Indonesia. Literacy pedagogy was rarely seen in campus life in which it was mostly applied at primary and secondary school levels. Therefore, this study explored the implementation process of critical literacy approach in learning English for EFL college students. An action research methodology was applied in this study involving six EFL college students. The study investigated the benefits and challenges of this teaching approach. The findings indicated that critical literacy approach could improve college students’ English proficiency and multiple skills, such as leadership, presentation, collaboration, self-contribution, respect, critical thinking, and expansion of multiple viewpoints through the discussion section. Improving English proficiency of college students and offering recommendations to EFL teachers for applying critical literacy approach in EFL class come as the expectation of the study.